Passive Stiffness of Left Ventricular Myocardial Tissue Is Reduced by Ovariectomy in a Post-menopause Mouse Model - Farré, Núria; Jorba, Ignasi; Torres, Marta; Falcones, Bryan; Martí-Almor, Julio; Farré, Ramon; Almendros, Isaac; Navajas, Daniel (Frontiers in Physiology, 2018)
BACKGROUND: Heart failure -a very prevalent disease with high morbidity and mortality- usually presents with diastolic dysfunction. Although post-menopause women are at increased risk of heart failure and diastolic dysfunction, poor attention has been paid to clinically and experimentally investigate this group of patients. Specifically, whether myocardial stiffness is affected by menopause is unknown. AIM: To investigate whether loss of female sexual hormones modifies the Young’s modulus (E) of left ventricular myocardial tissue in a mouse model of menopause induced by ovariectomy (OVX). METHODS: After 6 months of bilateral OVX, eight mice were sacrificed, fresh left ventricular myocardial strips were prepared (~8x1x1 mm) and their passive stress-stretch relationship was measured. E was computed by exponential fitting of the stress-stretch relationship. Subsequently, to assess the relative role of cellular and extracellular matrix components in determining OVX-induced changes in E, the tissues strips were decellularized and subjected to the same stretching protocol to measure E. A control group of 8 sham-OVX mice was simultaneously studied. RESULTS: E (kPa; m±SE) in OVX mice was ~2-fold lower than in controls (11.7±1.8 and 22.1±4.4, respectively; p<0.05). No significant difference between groups was found in E of the decellularized tissue (31.4±12.05 and 40.9±11.5, respectively; p=0.58). CONCLUSION: Loss of female sexual hormones in an OVX model induces a reduction in the passive stiffness of myocardial tissue, suggesting that active relaxation should play a counterbalancing role in systolic dysfunction in postmenopausal women with heart failure.